Faktor-Faktor yang Mempengaruhi Keparahan Derajat Infeksi Dengue pada Pasien Anak - Rahel, Clara Arta Uli; Apriliana, Ety; Septiani, Linda; Soleha, Tri Umiana (CV. Jasa Sukses Abadi, 2024)
Dengue infection is an infectious disease transmitted by mosquitoes, especially Aedes species which have been infected to humans. Dengue virus (DENV) consists of four serotypes, namely DEN-1, DEN-2, DEN-3, and DEN-4. Dengue virus infection in humans, especially in pediatric patients, can cause different symptoms from one patient to another. To make it easier to classify the patient's condition, WHO has classified the clinical severity of dengue infection, namely dengue fever, dengue hemorrhagic fever which consists of four levels, and dengue shock syndrome. The varying progression of dengue infection is the basis for knowing the factors that can influence the severity of the degree of dengue infection in terms of the patient's characteristics, clinical symptoms and laboratory results.